(untitled) (Research, Society and Development, 2022)
The objective of this work is to investigate corrosion and microstructure in self-adhesive cement composite with the replacement of the kid aggregate by glass residue. One of the most frequent pathologies found in reinforced concrete is corrosion of reinforcements that involves risks to the safety of the structure. Among the various techniques to study and evaluate corrosion in this work was chosen the electrochemical impedance spectroscopy (EIE) that characterizes a wide variety of electrochemical systems. Specimens were molded in the trace of 1:1:0,1:0.43 being a reference (without adding residue), others with substitution of 5%,15% and 20% in glass residue, in relation to the kid aggregate. The choice of the equivalent circuit was different depending on the number of materials used, for the reference sample a series resistive circuit was used with a second parallel circuit composed of an R resistance and a CPE phase element. For mixtures with glass residue, another R /CPE parallel circuit was added. Micrographs obtained through scanning electron microscopy (SEM) and X-ray dispersive energy spectrometry (EDS) were also performed.